THE EXPORT MARKETING STRATEGY OF CANNED FISH AT PT. SINAR PUREFOODS INTERNATIONAL IN THE CITY OF BITUNG - Manumpil, Ni Made V.A; Pangemanan, Sifrid S.; Pandowo, Merinda H. C. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2020)
Abstract: The trends that occur in the business world today indicate that competition between companies in making market opportunities more stringent. For that, the company must have a strong competitive base. One way to win the competition is to continue to improve the quality of products produced with solid quality and have the best quality, the company can continue to retain customers and even attract new customers because customers are the main target and benchmark for the companyâ€™s success. The purpose of this study is to find out the tuna export marketing strategy applied by PT. Sinar Purefoods International Bitung. The result of this study was from 10 informant workers handling export sales at PT.Sinar Purefoods International. The findings of this study reveal that five factors have a significant impact on marketing strategies: Products, Customers, Company Offering: Quality, Image, and after-sale service, Promotional Function, and Price / Selling Terms. The better the quality of the products produced, the company can get the trust and great opportunities in making export sales.Â Keywords: marketing strategy